The Potential of AFX Iliac Extension in Abdominal Aortic Aneurysms with High Iliac Tortuosity - Kikuchi, Yuta; Ohtani, Norifumi; Kamiya, Hiroyuki (International Journal of Angiology, 2021)
Recently, endovascular aortic aneurysm repair (EVAR) is the most common surgery for abdominal aortic aneurysm (AAA). However, iliac limb complications of EVAR often cause problems in patients with high iliac tortuosity. There is no difference of rate of iliac limb complication among EVAR devices, such as Excluder, Endurant, and Zenith in high iliac tortuosity. But there has been not reported about AFX. We studied AFX iliac extension as it is the only stent graft with an endoskeletal framework. This study aimed to evaluate the AFX iliac extension patency in a case in vitro and to use it in seven cases of AAA with high iliac tortuosity. The silicon tube inserted in the AFX iliac extension was flexed at 30, 60, 90, and 120 degrees, and the lumen of the iliac extension was monitored using an underwater camera in the circulatory system. During the experiment, the Iwaki Bellows Pump (IWAKI CO., LTD., Tokyo, Japan) produced a pulsating flow. We used this in seven patients with AAA high iliac tortuosity cases between November 2018 and May 2019. If the silicon tube inserted in the AFX iliac extension was flexed at 60 and 120 degrees, the stent protruded into the lumen. However, the graft was dilated at all degrees. All seven patients with AFX iliac extension had no complications and a patent iliac artery. The AFX iliac extension can reduce iliac limb complications in cases of high iliac tortuosity.
Keywords: endovascular aortic repair; AFX iliac extension; endoskeletal framework; iliac tortuosity; iliac limb complication; abdominal aortic aneurysm